Heavy metals removal from water by adsorption on propylthiol-functionalised mesoporous silica obtained by co-condensation. (11th February 2010) - Aguado, Jose; Arsuaga, Jesus M.; Arencibia, Amaya
Propylthiol-functionalised mesoporous silica SBA-15 prepared by co-condensation has been tested for heavy metal removal. Adsorption from aqueous solution was examined for Cu(II), Pb(II), Cd(II), and Hg(II). Adsorption isotherms were determined at 20°C and Langmuir and Freundlich models were fitted to experimental data. The results from adsorption experiments indicate that mercury is efficiently removed from water. Copper, lead and cadmium uptakes from aqueous solution are noticeable but significantly smaller than mercury removal; moreover, lead and cadmium adsorption isotherms exhibit no adsorption maximum within the investigated range of concentration. The influence of solution pH on lead adsorption was also investigated.